2022
DOI: 10.3389/fphar.2022.962596
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity associated with immune checkpoint inhibitors: Current status and future challenges

Abstract: Immune checkpoint inhibitors (ICIs) are the most notable breakthrough in tumor treatment. ICIs has been widely used in tumor patients, but its wide range of immune-related adverse events (irAEs) should not be ignored. irAEs can be involved in any organ system, including immune-related cardiotoxicity. Although the cardiotoxicity induced by immune checkpoint inhibitors is rare, it is extremely lethal and has attracted increasing attention. PD-1 and PD-L1 are expressed in human cardiomyocytes, so the application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Although rare, ICIs-related cardiovascular events can occur in cancer patients ( 12 ). Events of inflammatory myocarditis, vasculitis and endothelitis are seen in clinical practice and some of them may be at high mortality ( 12 , 13 ). Non-viral inflammatory myocarditis is the most observed cardiotoxic event in patients on ICIs, however the frequency is extremely low (<1%) ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, ICIs-related cardiovascular events can occur in cancer patients ( 12 ). Events of inflammatory myocarditis, vasculitis and endothelitis are seen in clinical practice and some of them may be at high mortality ( 12 , 13 ). Non-viral inflammatory myocarditis is the most observed cardiotoxic event in patients on ICIs, however the frequency is extremely low (<1%) ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an ICI, durvalumab causes immune-mediate adverse events (imAEs), pneumonitis, thyroid disorders, and dermatitis/rash, with diarrhea/colitis being the most common [ 4 , 5 ]. Rarely, durvalumab can be associated with cardiac imAEs, including myocarditis, pericarditis, arrhythmias, and coronary vasculitis [ 6 ]. As per Mahmood SS's multicenteric observational study, the estimated incidence of ICI-myocarditis is 1.14% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor immunotherapy is an important clinical strategy for the treatment of various solid and hematological malignancies [ 1 ]. Immune checkpoint inhibitors (ICIs) are immunotherapies that boost anticancer immune responses by targeting receptors on the surface of T-lymphocytes [ 2 ]. In other words, they redirect the host immune system toward fighting off tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, fulminant and fatal toxic effects, such as hepatitis and cardiotoxicity, have been described [ 4 ]. Cardiovascular-related events may present as arrhythmias, pericardial disease, vasculitis, myocardial infarction, and Takotsubo cardiomyopathy, with the most common being myocarditis [ 2 ]. A retrospective study of data from eight clinical centers found that the prevalence of myocarditis was 1.14% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation